2010
DOI: 10.2147/cia.s10223
|View full text |Cite
|
Sign up to set email alerts
|

Functional mobility and balance in community-dwelling elderly submitted to multisensory versus strength exercises

Abstract: It is well documented that aging impairs balance and functional mobility. The objective of this study was to compare the efficacy of multisensory versus strength exercises on these parameters. We performed a simple blinded randomized controlled trial with 46 community-dwelling elderly allocated to strength ([GST], N = 23, 70.2-years-old ± 4.8 years) or multisensory ([GMS], N = 23, 68.8-years-old ± 5.9 years) exercises twice a week for 12 weeks. Subjects were evaluated by blinded raters using the timed ‘up and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 27 publications
5
49
0
5
Order By: Relevance
“…This observation is consistent with results in previous studies that applied interventions with similar principles used in the BEC and with the same amount of sessions (Eyigor et al 2007;Donat and Ozcan 2007;Fu et al 2009;Alfieri et al 2010). However, these authors had superficially described the types of exercises and stimuli, only in a broad way, reporting only the total duration of sessions, which was approximately 50 to 60 min.…”
Section: Discussionsupporting
confidence: 90%
“…This observation is consistent with results in previous studies that applied interventions with similar principles used in the BEC and with the same amount of sessions (Eyigor et al 2007;Donat and Ozcan 2007;Fu et al 2009;Alfieri et al 2010). However, these authors had superficially described the types of exercises and stimuli, only in a broad way, reporting only the total duration of sessions, which was approximately 50 to 60 min.…”
Section: Discussionsupporting
confidence: 90%
“…In their systematic review, Granacher et al (2013) intended to evaluate new intervention programs that were specifically designed to work against age-related impairments. Studies considered in this review showed positive effects of movements of everyday life in combination with balance exercises (Alfieri et al 2010;Egerton et al 2009;Mayer et al 2011). However, studies that implemented traditional resistance training without any additional exercises also displayed comparable positive effects (Aagaard et al 2010;Barry and Carson 2004;Bottaro et al 2007;Manini et al 2007).…”
mentioning
confidence: 85%
“…Previous work has suggested that there was a significant effect of gender on strength and endurance that may be resulted from agerelated loss of muscle mass in elderly females more than males 31,32 . These changes are known as sarcopenia 33,34 .…”
Section: Discussionmentioning
confidence: 99%